Characterization and function analysis of a novel gene, Hc-maoc-1, in the parasitic nematode Haemonochus contortus. Issue 1 (December 2017) - Ding, Haojie; Shi, Hengzhi; Shi, Yu; Guo, Xiaolu; Zheng, Xiuping; Chen, Xueqiu; Zhou, Qianjin; Yang, Yi; Du, Aifang
Abstract Background Enoyl-CoA hydratase (MAOC) is required for the biosynthesis of the fatty acid-derive side chains of the ascarosidevia peroxisome β-oxidation in the free-living nematodeCaenorhabditis elegans . The derivative of dideoxy-sugar, ascarylose is used as dauer pheromones or daumones to induce development of the stress-resistant dauer larvae stage. Methods Hc-maoc-1 gene was obtained by searching the Wellcome Trusts Sanger Institute'sH. contortus genomic database. qRT-PCR was performed to analyse the transcriptional levels ofHc-maoc-1 with different developmental stages as templates. IFA was carried out to determine the expression pattern in L3 larvae and micro-injection was used to verify the promoter activity of 5′-flanking region ofHc-maoc-1 . Overexpression and RNAi experiments were applied in N2 strain to ascertain the gene function ofHc-maoc-1 . Results The full-length cDNA ofHc-maoc-1 was 900 bp in length, which contained eight exons separated by seven introns and possessed the Hotdog domain and the MaoC-like domain, together with several other residues and a hydratase 2 motif. It was transcribed throughout the lifecycle and peaked in the fourth-stage larvae (L4) ofH. contortus ; however, its transcription level decreased in diapausing L4. The protein expression and location of Hc-MAOC-1 were mainly in the intestine of L3 larvae. Overexpression ofCe-maoc-1 andHc-maoc-1 inC. elegans showed extended lifespan and increased body size. The protein Ce-MAOC-1 and Hc-MAOC-1 were localized in the intestine with a punctate pattern. InC. elegans, knockdown ofCe-maoc-1 conferred shortened lifespan and body lengths, decreased brood size and increased lipid storage. Conclusion Caenorhabditis elegans was used as a model organism to ascertain the function ofHc-maoc-1 inH. contortus . Our results showed the similar characteristics and functions withCe-maoc-1 and provided evidences of the potential functions ofHc-maoc-1 in biosynthesis of daumones inH. contortus .